THE TRANSLATION ANALYSIS OF IDIOMATIC EXPRESSSIONS IN THE FILM ENTITLED TROPIC THUNDER - IQBAL, Muhammad (2009)
Idiom is the expression which most of the times are represented in the films. However, it is quite hard to translate the idioms from one language into another one. Considering that issue, the conducted study is entitled THE TRANSLATION ANALYSIS OF IDIOMATIC expressionS IN THE FILM ENTITLED TROPIC THUNDER which is aimed at finding out the methods of translation employed by the translator in translating the idiomatic expressions and the types of idiomatic expressions which are mostly used in the film. This study uses a descriptive qualitative method. The findings of the research shows that types of idioms mostly used in the film entitled Tropic Thunder are slang (43%), figures of speech (18%), English phrasal compounds (17%), substitute (13%), proper names (7%), and abbreviation (2%). The result of this study also indicates that several methods were applied in translating the idiomatic expressions: communicative translation (32%), literal translation (28%), semantic translation (27%), and faithful translation (13%). The writer puts forward some suggestions as follows: the further research should investigate the idiomatic expressions by using procedures of translation or strategies of translation, the context idiomatic expressions should also be investigated since idioms have different meanings.